Analisis Usahatani Tanaman Sela Pada Lahan Perkebunan Kelapa Di Desa Tontalete Kecamatan Kema Kabupaten Minahasa Utara - Mawuntu, Ignacia Mariana; Pangemanan, Lyndon Reindhart Jacob; Jocom, Sherly Gladys (AGRI-SOSIOEKONOMI, 2024)
This research aims to analyze the income of farmers who cultivate land under coconut trees with intercropping. This research uses primary data and secondary data. Primary data is a source of data obtained directly from original sources or not through intermediaries. Meanwhile, secondary data is data sourced from the Tontalete Village office, Kema District, North Minahasa Regency and the Central Statistics Agency (BPS). Sampling was carried out randomly (Simple Random Sampling). The total research sample was 13 corn farmers and 2 chili farmers. The research results were analyzed using farming income analysis. The results of this study show that farmers utilizing coconut plantation land with intercropping in Tontalete Village, Kema District, North Minahasa Regency, obtained an average production cost of corn intercropping respondents amounting to IDR8.445.822,00 per hectare, with revenue of IDR21.868.750,00 per hectare, resulting in an income of IDR13.422.929,00 per hectare. Meanwhile, respondents growing intercropped chili had an average production cost of IDR10.865.342,00 per hectare, with revenue of IDR69.307.857,00 per hectare, and income of IDR58.442.515,00 per hectare over 8 harvesting periods.